The "neuro" of neuroblastoma: Neuroblastoma as a neurodevelopmental disorder. Issue 1 (30th April 2016) - Ratner, Nancy; Brodeur, Garrett M.; Dale, Russell C.; Schor, Nina F.
Abstract : Neuroblastoma is a childhood cancer derived from cells of neural crest origin. The hallmarks of its enigmatic character include its propensity for spontaneous regression under some circumstances and its association with paraneoplastic opsoclonus, myoclonus, and ataxia. The neurodevelopmental underpinnings of its origins may provide important clues for development of novel therapeutic and preventive agents for this frequently fatal malignancy and for the associated paraneoplastic syndromes. Ann Neurol 2016;80:13–23